Mengurai Kurikulum Pendidikan Ilmu Sosial (Social Science Education) di Negara Ukraina: Apakah ada Relevansi dan Implikasi Untuk Kurikulum Pendidikan IPS di Indonesia? - Salman Alparis Sormin; Erlina Wiyanarti; Dharma Gyta Sari Harahap; Muhammad Yusuf Ritonga; Siti Maryam Pane (Mathematics Education Study Program, 2025)
This article is a comparative study of the social science education curriculum in Ukraine and its implications for the social studies curriculum in Indonesia. Ukraine, which experienced a major transformation in its education system after its independence from the Soviet Union, has adopted a competency-based approach that focuses on the development of critical thinking skills, civic values, and global awareness. This curriculum is designed to form patriotic citizens who are able to adapt to local and global dynamics, with the integration of European educational standards. On the other hand, social studies education in Indonesia emphasizes more on strengthening the values ​​of Pancasila, national insight, and cultural diversity. This article uses a literature study method to analyze the relevance and possibility of adopting elements of the Ukrainian curriculum into social studies education in Indonesia. The results of the analysis show that the Ukrainian competency-based approach can enrich the Indonesian social studies curriculum, especially in the development of analytical skills, understanding of democracy, and adaptation to global challenges.